University Bureaucracies as the Death of Play: The 1968 Strax Affair and the Arts of Discombobulation - Dressler, Harrison; Pleshet, Noah; Tubb, Daniel (Critical Education, 2025)
The bureaucratic precepts engendered by modern universities produce a slew of negative effects inimical to educational justice. Drawing on historiographical evidence from the 1968 Strax Affair, a little-known protest held at the University of New Brunswick, we identify the arts of discombobulation as a novel approach to challenge the intellectual constraints imposed by university bureaucracies. By theorizing the arts of discombobulation, we aim to counteract bureaucracy’s most alienating affective residues, equipping scholars with an administrative arsenal capable of transforming the corporate academy into a playful, joyful environment. Inspired by cultural historian Johan Huizinga’s theory of the “play-function,” we introduce five interrelated tactics—burlesque versions of both formal and informal administrative practices—that amplify the contradictions inherent to the corporate academy’s contemporary bureaucratic structure: personalization, befuddlement, signal jamming, mapping, and abeyance. Even during moments of Kafkaesque bureaucratic defeat, discombobulation can generate a sense of heightened play necessary to fuel democratic resistance.